Cognitive Web (International Journal of Current Engineering and Technology, 2015)
Our final year project is titled ‘Cognitive Web’ and helps the user to discover interesting stuff quickly on the Internet. Using a combination of human opinions and machine learning, Cognitive Web presents registered users with only web sites that have been suggested by other like-minded users. With time, the database will recognize user’s patterns of interest, and suggest the web pages accordingly. Cognitive web is an intelligent and helpful way to make the Internet a compact and more intimate place. This project helped us to master the complexities of database management and also provided further exposure to us in the field of Artificial Intelligence.
Keywords: Cognitive web; Opinion Mining; Artificial Intelligence